Sleep, cardiometabolic health, and neurocognitive performance in esports players - Kemp, Chadley (Department of Human Biology, 2025)
Esports players represent a growing and maturing population within the primary demographic of general video gamers, with a proclivity to engage with a high volume (i.e., dose, duration, and frequency) of video gaming activities. Accordingly, esports players are typically characterized by unique behaviors, including prolonged exposure to blue light from electronic screens, extended periods of sedentary behavior, irregular sleep patterns due to late-night matches or competitions, and high levels of stress, all of which may be undertaken to improve or maintain their competitive status. However, the concern is that these behaviors may, in turn, impact esports players' sleep, circadian rhythms, and physical and mental health over time. Despite the growing popularity of esports among adults, few studies have investigated the relationships between sleep, cardiometabolic health, and neurocognitive performance in this population. Specifically, the vast majority of existing research on gaming and health has focused on children and adolescents, leaving a significant gap in our understanding regarding the potential health risks associated with regular high-volume gaming behaviors in adults. Relatedly, adult esports players might also be more vulnerable to the downstream effects of pathological (i.e., prolonged and excessive) gaming behaviors, given their implicit cardiometabolic disease risk susceptibility, which is attributable to aging but also unhealthy lifestyle behaviors and substance addictions like smoking and alcohol. To address the gap in the literature, this thesis aims to investigate the associations between devicederived sleep patterns, white light exposure, cardiometabolic health status, and neurocognitive performance in adult esports players. In addition, the thesis will describe device-derived quantitative doses and 24-hour profile patterns of physical activity and white light exposure in these individuals. The work underlying this thesis is intended to be a stepping stone toward health regulation in gaming and esports, for which motives are to support individual decisions, governments, and policy makers through awareness and by providing evidence-based recommendations to adopt and maintain healthy gaming behaviors to ameliorate chronic health problems.